삼킴 과제에 따른 한국 노년층의 혀압력 특성 - 최성희(Seong Hee Choi); 김향희(HyangHee Kim); 최철희(Chul-Hee Choi); 서해니(Hae Ni Seo); 박채림(Chae Rim Park) (Audiology and Speech Research, 14(3), 2018)
Purpose: The purpose of this study was to investigate tongue pressures of the elderly as a function of oral swallowing in swallowing tasks and tongue bulb locations. Methods: Tongue pressures were compared between 2 locations (left vs. right) and also among 3 locations (anterior, medial, and posterior) of the tongue using the Digital Swallowing Workstation tongue bulb manometry system (KayPENTAX) in 20 young adults and 20 healthy older adults during dry swallow and 5 mL water swallow. Results: Swallowing pressures significantly differed by task with higher pressure in dry swallow than in 5 mL water swallow. Older adults demonstrated significantly reduced tongue pressures during dry swallow than did young adults, whereas no group differences were observed during 5 mL water swallow. While no differences were found between the left and right of the tongue in either group, significantly greater tongue pressures were noted in the anterior compared with the middle or posterior portions. Furthermore, a negative relationship between tongue pressure and the Dysphagia Handicap Index was seen in older adults during dry swallow. Conclusion: Age-related differences in terms of tongue pressures were evident only during dry swallow with a decline of the anterior tongue pressure amplitude. This study is significant in that it delineated the task and tongue bulb location-specific performance of swallowing in older adults. KCI Citation Count: 3